Exploring the Potential of Antibiotic Production From Rare Actinobacteria by Whole-Genome Sequencing and Guided MS/MS Analysis - Hu, Dini; Sun, Chenghang; Jin, Tao; Fan, Guangyi; Mok, Kai Meng; Li, Kai; Lee, Simon Ming-Yuen (Frontiers in Microbiology, 2020)
Actinobacteria are well recognized for their production of structurally diverse bioactive secondary metabolites, but the rare actinobacterial genera have been underexploited for such potential. To search for new sources of active compounds, an experiment combining genomic analysis and tandem mass spectrometry (MS/MS) screening was designed to isolate and characterize actinobacterial strains from a mangrove environment in Macau. Fourteen actinobacterial strains were isolated from the collected samples. Partial 16S sequences indicated that they were from six genera, including Brevibacterium, Curtobacterium, Kineococcus, Micromonospora, Mycobacterium, and Streptomyces. The isolate sp.01 showing 99.28% sequence similarity with a reference rare actinobacterial species Micromonospora aurantiaca ATCC 27029T was selected for whole genome sequencing. Organization of its gene clusters for secondary metabolite biosynthesis revealed 21 clusters encoded to antibiotic production, which is higher than other Micromonospora species. Of the genome-predicted antibiotics, kanamycin was found through guided MS/MS analysis producible by the M. aurantiaca strain for the first time. The present study highlighted that genomic analysis combined with MS/MS screening is a promising method to discover potential of antibiotic production from rare actinobacteria.